(untitled) (Academia Science Repository, 2023)
Each profession must be performed at a high level, meet the requirements of professional skills. Pedagogical skill refers to the high degree of manifestation of the abilities of a coach in pedagogical activity, the orientation of his entire being to education. Pedagogical skill is formed on the basis of study-learning, exercise, experiences for a long time. The difference between pedagogical skills and other professional skills is that it is divided into several edges. In this article, opinions and reflections are made on the culture of communication and the role of abilities in pedagogical activity.